Does Supply Chain Analytics Enhance Supply Chain Innovation and Robustness Capability? - Shamout Mohamed Dawood (Organizacija, 2019)
Background and purpose: Little are known about the nature of the interaction between supply chain analytics, supply chain innovation and robustness capability. The purpose of this paper is to examine the effectiveness of supply chain analytics in enhancing firms supply chain innovation and robustness capability in the Arabian context.